AGROECOYSTEM ENGINEERING THE USE OF REFUGIA PLANTS IN MANAGING PEST POPULATIONS OF ONION PLANTS (Allium ascalonicum L.) - M Farhan Abdul Aziz; Tri Yaninta Ginting; Desi Sri Pasca Sari Sembiring (RADJA PUBLIKA, 2024)
Shallots (Allium ascalonicum L.) is one of the horticultural commodities that has an important role in the Indonesian economy. One of the main threats to this plant is the attack ofthe pest Spodoptera exiguawhich can cause significant damage, especially at heavy infestation rates resulting in leaves drying out and falling prematurely. In an effort to control the population of this pest, one planting pattern system that can be usedThe intercropping system uses refugia plants such as marigold flowers (Tagetes erecta L.) and zinnia (Zinnia elegans), which act as shelters for natural enemies of pests, including predators and parasitoids. This study aims to evaluate the ability of refugia plants in controlling pest attacks on intercropped onion plants. The results showed thatat the observation of Week 1 no intensity of attacks occurred. In weeks 2, 3, 4, and 5 there were attacks with the highest attack intensity was 1.25% in P0 treatment and the lowest attack intensity in P2 treatment.Meanwhile,P1 and P2 treatment showed lower pest population densities compared to P0.P0 treatment shows the highest pest population density compared to other treatments. In addition, arthropod diversity analysis resultedan index of 2.07%,indicating the level of species diversity that is in the refugia intercropping system.Because the percentage of attacks of such treatment ranges from>0-≤10%.